Characteristics of diurnal ventricular premature complex variation in right ventricular outflow tract arrhythmias after catheter ablation. Issue 15 (April 2017) - Jhuo, Shih-Jie; Lo, Li-Wei; Chang, Shih-Lin; Lin, Yenn-Jiang; Chung, Fa-Po; Hu, Yu-Feng; Chao, Tze-Fan; Tuan, Ta-Chuan; Liao, Jo-Nan; Lin, Chin-Yu; Chang, Yao-Ting; Lin, Chung-Hsing; et al.
Abstract : Abstract: Diurnal variations in ventricular tachyarrhythmias (VAs) have been demonstrated in idiopathic arrhythmogenic heart disease. The electrophysiological characteristics of diurnal variations in idiopathic right ventricular outflow tract (RVOT) VA have not previously been elucidated. Sixty-two consecutive patients undergoing catheter ablation for idiopathic RVOT VA (mean age: 42.8 ± 12.3 years, 35 females) were enrolled. The diurnal variation type (group 1, n = 36) was defined as those patients who had most ventricular premature contractions (VPCs) during the night hours by preprocedure Holter recordings. Group 2 (n = 26) was defined as those patients who did not have significant VPC variations. The baseline characteristics and electrophysiological properties were collected and analyzed, and the rates of recurrence after catheter ablation were compared between the 2 groups. In this study, heart rate variability analysis demonstrated lower low frequency/high frequency ratios in group 1 than in group 2 (3.95 ± 3.08 vs 6.26 ± 5.33; P = 0.042). There were no significant differences in baseline characteristics, echocardiography and electrophysiological characteristics between the 2 groups. During a mean follow-up period of 13.5 ± 11.0 months, a total of 16 patients had VA recurrences, including 13 patients from group 1 and 3 patients from group 2 (36.1% vs 12.5%, P = 0.039). This study demonstrated the effect of the autonomic nervous system in idiopathic RVOT VAs and that the diurnal variation type leads to a higher recurrence rate after catheter ablation.